2008
DOI: 10.1634/theoncologist.13-s3-21
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Aggressive Tumor Phenotype: Implications for Therapy and Prognosis

Abstract: Tumor hypoxia, mostly resulting from poor perfusion and anemia, is one of the key factors in inducing the development of cell clones with an aggressive and treatment-resistant phenotype that leads to rapid progression and poor prognosis. Studies in patients with solid tumors suggest that there is a range of hemoglobin (Hb) concentrations that is optimum for tumor oxygenation. When used to achieve an Hb level within this range, erythropoiesis-stimulating agents (ESAs) can be expected to increase tumor oxygenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
262
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(271 citation statements)
references
References 31 publications
5
262
1
3
Order By: Relevance
“…Hypoxia is considered to be a potential barrier for treating tumors because it induces the development of cell clones with an aggressive and treatment-resistant phenotype, which leads to rapid progression and poor prognosis (Kizaka-Kondoh et al, 2003;Vaupel, 2008). It has been shown that hypoxia can decrease the therapeutic efficacy of radiation treatment, surgery, and some forms of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia is considered to be a potential barrier for treating tumors because it induces the development of cell clones with an aggressive and treatment-resistant phenotype, which leads to rapid progression and poor prognosis (Kizaka-Kondoh et al, 2003;Vaupel, 2008). It has been shown that hypoxia can decrease the therapeutic efficacy of radiation treatment, surgery, and some forms of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor hypoxia, mostly resulting from poor perfusion and anemia, is one of the key factors involved in the development of cell clones with an aggressive and treatment-resistant phenotype, which leads to rapid progression and poor prognosis (Semenza, 2001;Poellinger and Johnson, 2004;Vaupel, 2008). It has been reported that solid tumors in humans, even those less than 1 cm in diameter (i.e., at the limits of clinical detection), may have substantial hypoxic fractions (Bae et al, 1999).…”
mentioning
confidence: 99%
“…Hypoxia is a characteristic feature of locally advanced tumours and is coupled to tumour invasiveness, poor survival and treatment failure in cancer patients 21 . The cellular adaptation to hypoxia may also contribute to loss of polarity, tissue integrity and architecture.…”
mentioning
confidence: 99%
“…10,11 Hypoxia has also been found to result in cells with more aggressive phenotype, thereby increasing tumour malignancy. 12 In addition to tumour spheroids, micro-dissected tumour tissues have also been recently demonstrated to survive in culture within a microfluidic a) S. M. Grist and S. S. Nasseri contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%